2013
DOI: 10.7461/jcen.2013.15.3.145
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of the Superficial Temporal Artery in Adult Koreans Using 3-Dimensional Computed Tomographic Angiogram: Clinical Research

Abstract: ObjectiveThe increased use of bypass surgery in the treatment of ischemic cerebrovascular diseases requires a better understanding of the superficial temporal artery (STA) anatomy. This study is to describe the gross anatomy of STA in adult Korean population with respect to cranial surgery and to provide basic anatomic data for bypass surgery.MethodsThe study evaluated retrospectively 35 patients who visited the neurosurgery department at a single institution. For each patient, both the left and right STA (70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 6 publications
5
29
0
1
Order By: Relevance
“…This result is similar to previous research9). STA sparing was possible in all surgeries and may confer several advantages such as the reduction of subgaleal hematoma and stimulation of wound healing.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to previous research9). STA sparing was possible in all surgeries and may confer several advantages such as the reduction of subgaleal hematoma and stimulation of wound healing.…”
Section: Discussionsupporting
confidence: 91%
“…The presence or absence of the ''C'' shape half-buttonhole should be helpful for pre-operative planning of the anterior-posterior course of the STA. Our series showed a higher rate of STA bifurcations occurring above the zygomatic arch (96 %), compared to 75-90 % seen in the literature [5,9]. We demonstrate here that CTA is a non-invasive imaging technique that provides excellent B bifurcation of STA.…”
Section: Resultsmentioning
confidence: 41%
“…After this point, the artery typically bifurcates into frontal and parietal branches, but occasionally the STA may either continue as a single vessel to either the frontal or parietal regions or have additional frontal or parietal branches [8]. In approximately 10-25 % of people, the STA bifurcation is located at or below the level of the zygomatic arch [5,9]. A recent 3D-computed tomography angiography (CTA) study of 53 pts showed the STA bifurcation to be more commonly located over the posterior third of the zygomatic arch (58 %), followed by above the zygomatic arch (40 %), and below the zygomatic arch (2 %) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The superficial temporal artery is one of the external carotid artery branches mainly feeding the scalp (4,5). The other branches of the external carotid artery are the facial artery, maxillary artery, occipital artery, and the posterior auricular artery.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial temporal artery is one of the external carotid artery branches which has the duty of scalp feeding (4,5). Facial artery, maxillary artery, occipital artery and posterior auricular artery are other arteries as they feed the scalp (6,7).…”
Section: Introductionmentioning
confidence: 99%